Difficulties in the Prevention of Violence Against Children - Frontera Izquierdo, Pedro (Razón y fe, 2025)
The Convention on the Rights of the Child recognizes that all children have the right to be free from all forms of violence. Violence against children has strong, long-lasting effects on brain function, mental health, high risk behaviors and social disfunction. Difficulties in understanding how to fight and prevent violence against children are described, based on the experience of the author and on an updated bibliography, including physical and sexual abuse, neglect, bullying and cyberbullying. Knowledge of the circumstances associated with child maltreatment may help in the prevention with early interventions but is a complex problem with no single cause and no single solution. The strategies are: implementation and enforcement of laws, education in norms, values and skills, support services helping children heal, access to justice and social and economic support to parents.